Host-controlled Restriction of T-even Bacteriophages: Relation of Endonuclease I and T-even-induced Nucleases to Restriction - Molholt, Bruce (1968)
Restriction of nonglucosylated T2 phage (T(*)2) as a function of bacterial growth state was the same for endonuclease I-containing and endonuclease I-deficient strains of Escherichia coli B. Furthermore, E. coli strains with various levels of restriction for T2 had comparable endonuclease I activities. It was also found that a T4 mutant temperature-sensitive for gene 46 and 47 functions was fully restricted at 42 C. It therefore appears that neither endonuclease I nor the phage-induced nucleases whose activities are blocked by mutations in genes 46 and 47 catalyze the initial event in restriction of nonglucosylated T-even phages.